Draft Sixth Five Year Plan 1980-1985 Administration of Union Territory of Dadra and Nagar-Haveli - Planning Commission (Planning Commission, 1980)
This being a rural area the occupation of the people is Agriculture and therefore, emphasis is continued to be laid on the Development of Agriculture sector. Under the Agriculture Sector the existing schemes of subsidy and loan for distribution of seeds, manure, fertiliser, Plant protection equipments, commercial crops, fruit-grafts, agriculture implements, oil engine, etc. are proposed to be continued. Schemes providing for study tours, incentive for adoption of change of method of Paddy cultivation, holding of Khedut Shibir, Demonstration of Agriculture practices, agriculture education etc.
Administration of Union Territory of Dadra and Nagar-Haveli